SCOUT EDUCATIONAL METHOD AND TRANSDISCIPLINARITY: CONTRIBUTIONS TO ENVIRONMENTAL EDUCATION (CIPEEX, 2023)
Founded by Baden-Powell, scouting, being non-formal education, allows its members to value theenvironment, preparing them for preservation and sustainable development. In this study, the practiceof scouting and its socio-environmental and educational benefits for children and adolescents of theBernardo Sayão Scout Group were analyzed through the Reduce, Recycle, and Reuse (3R's) badgeactivity. Bibliographic and field research was conducted, with a qualitative approach. The theoreticalframework was based on the concepts of Scouting, Environmental Education, Non-formal Education,and Transdisciplinary Education. Technical visits were conducted weekly to the Scout Group fromOctober to November 2022. For four months, the scouts collected PET bottle caps and participated inworkshops. With the guidance of a Scout Leader, they crafted with the bottle caps: tic-tac-toe, pencilholder, fidget spinner, cup and plate holder. The scouts evaluated the discarded material regarding theenvironment and realized the importance of responsible consumption and the reuse of bottle caps. Thisresearch demonstrated that the scouting method is a transdisciplinary education that cares about andcarries out activities related to environmental and sustainability issues, such as the 3R's Badge,promoting sustainable habits for an ecological and healthy lifestyle.
Keywords: Earth Tribe activity; sustainable development; environmental and transdisciplinary education; scout educational method